A hyperspectral imaging system for in vivo optical diagnostics. - Tuan Vo-Dinh (IEEE Engineering in medicine and biology magazine)
This paper details the basic principles and instrumental systems as well as applications of hyperspectral imaging system in the biomedical field. The development of an HSI system that combines recent advances in several photonic technologies, including an AOTF, a 2-D CCD detector, and imaging fiber optics. The integration of these technologies leads to a versatile and powerful imaging system that can rapidly record spectral images of samples. This imaging system could find useful applications in medical diagnostics applications where rapid in vivo detection of complex samples is required. The HSI technique has the potential for in site optical diagnosis on tissue and it can be use for guidance of surgical intervention and treatment. The optical diagnostic approaches may either be an imaging modality or a spectroscopic modality. The spectroscopic diagnostics may also provide real-time assessment of tissue response to therapy.